Contribuições da Escola Estadual de Ensino Médio Paulo Freire no processo de formação política de jovens de assentamentos do município de Abelardo Luz/SC - Wegher, Joarez Luiz (2019)
This research aims to analyze the contributions of State High School Paulo Freire in the process of political education of young settlers and to identify the relationship between this education and the struggle for the establishment of a Field School. It holds the following specific objectives: to analyze the school’s training intentionality and its relationship with dominant ideology and/or the building of a counter-hegemonic training process; to study the school’s contribution and its relationship to the Brazilian landless social movement MST along with the political education process of young settlers; to identify the Paulo Freire school’s characteristics that may relate to paradigms for building Field Schools, and unveil some existing contradictions in a possible movement where there is a transition from a Rural School to a Field School and its implications along with the political education process of young settlers. This master thesis, marked by qualitative traits, used as tools for data collection school observations, analysis of its Political Pedagogical Project, and semistructured interviews with twelve young students from K-12 and six educators. It is divided into three main parts. The first one seeks to portrait the struggle for land in Brazil and how the landless movement MST was created. The second one aims to understand the studied schools as a space of struggle, conflicts, and to see how the occupation of the School by MST and the constitution of a Field Education are part of the struggle the rural workers fight for a school that is different from the capitalistic one, and for a new society. In this struggle, young people’s political education has become critical. The third and last part takes into consideration the political education of youth in the Paulo Freire school, located in the municipality of Abelardo Luz, in Santa Catarina state, Brazil, and its relationship to MST and Field Education. We conclude that the MST participation along with the studied school takes place mainly via its political pedagogical proposal. It is present in the work at the school which is based on the Study Complex. This Study Complex is grounded in the philosophical and pedagogical principles of both MTS’s pedagogy and the Russian Socialist pedagogy. From this pedagogies, the cited school contributes to the political education of youth, standing out the work by the Core Centers, that enables these young people self-organization. In an attempt to build an alternative school, Paulo Freire school contributes to the implementation of a Field School, especially by establishing school education as a right and reinforcing the permanent need for school occupation. Therefore, the school is reinforced by our study as a space of struggle, the terrain where contradictory forces are confronted, and therefore it is open to action.